PERENCANAAN PEMBELAJARAN BERBASIS PERMAINAN TRADISIONAL SEBAGAI IMPLEMENTASI LITERASI BUDAYA PADA ANAK USIA DINI - Buadanani B; Delfi Eliza (UIR PRESS, 2022)
Traditional games in early chilhood are a form of implementing the noble culutures of the nation in students so that cultural literacy is embedded from an early age. Traditional game-based learning can be a solution for the realization oof cultural literacy. This article provides views regarding the preparation of traditional game-based learning plans. The writing of this article uses a literature review approach. The result of study concluded that traditional game-based learning planning can be done by adjusting children’s development by integrating in the process of opening, core and closing learning activities.